Father- and Youth-Reported Family Affective Expression Differentially Predicts Youth Internalizing and Externalizing Symptoms. (21st December 2018) - Rabinowitz, Jill A.; Osigwe, Ijeoma; Byrne, Ashley; Drabick, Deborah A. G.; Reynolds, Maureen D.
Abstract : Temperamental approach is associated with adolescent internalizing and externalizing symptoms. Negative family affective expression, or problematic communication about emotions, is also associated with youth's risk for symptoms. However, it is unclear whether negative family affective expression differentially predicts symptoms based on (a) youth's temperamental approach and (b) informants' perceptions of negative family affective expression. To address these issues, we explored whether mother-, father-, and youth-reported negative family affective expression moderated the relation between youth temperamental approach and symptoms. Participants were 775 youths (71% male, 76% Caucasian) assessed at ages 10–12 (Time 1) and 12–14 (Time 2). Mothers, fathers, and youths reported on negative family affective expression and youths reported on temperamental approach at Time 1. Teachers reported on youth symptoms at Times 1 and 2. Youth- and father-reported, but not mother-reported, negative family affective expression moderated the relation between youth approach and symptoms. When youths reported higher negative family affective expression, youths lower in approach exhibited higher internalizing symptoms than youths higher in approach. In contrast, when fathers reported lower negative family affective expression, youths lower in approach exhibited higher internalizing and externalizing symptoms than youths higher in approach. Assessments and interventions for youth symptoms should include not only temperamental features, but also multiple informants' perspectives of family affective expression. Such efforts could promote greater family communication, address problematic family dynamics, and potentially attenuate risk for youth symptoms.